Dengue protease inhibition activity of selected malaysian medicinal herbs - Salleh, H.M.; Chong, Soon Lim; Othman, Rozana; Hazni, Hazrina; Ahmad, Khadher; Mohd Yusoff, Mohd Yakub @ Zulkifli; Fauzi, Nurulwahidah; Wahab, Habibah A.; Liew, Sook Yee; Awang, Khalijah (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Dengue fever is one of major health problem around the world including Malaysia. It is caused by the arthropode-borne flavivirus and transmitted by the bite of the Aedes aegypti or Aedes albopictus mosquito infected with one of the four dengue virus serotypes (DENV-1, DENV-2, DENV-3, or DENV-4). In this study, a screening exercise of various Malaysian medicinal plants showed that the extracts of Lawsonia inermis, Dryobalanops aromatica, Punica granatum, Zizyphus jujuba Lam. and Zingiber zerumbet exhibited potent inhibitory activity against NS2B-NS3 serine protease. The methanol extracts of Dryobalanops aromatica showed inhibition of 99.70 % at concentration of 200 µg/mL with IC50 value of 0.30 ± 0.16 µg/mL. © 2019, Malaysian Society for Parasitology. All rights reserved.